Secure OPC UA Server configuration for smart charging stations - Schindler, Josef; Kirdan, Erkin; Waedt, Karl (Lecture Notes in Informatics (LNI), Proceedings - Series of the Gesellschaft für Informatik (GI), 2021)
Direct-To-Consumer (D2C) marketing recently gains popularity in society by bypassing unnecessary mediators and thus avoiding cost. In Information and Communication Technology (ICT) terms, it is comparable with Machine-To-Machine (M2M) communication overcoming additional mediators, i.e. remote servers. In this paper, we research M2M communication for battery boosted charging station. Therefore, we consider a setup comprising an OPC Unified Architecture (OPC UA) Client and OPC UA Server. The server represents the smart charging station, where the client can reserve time slots for charging sessions. In this paper, we answer how to facilitate this using the different services provided by OPC UA. Additionally, we apply an OPC UA Metasploit module on two differently - according to the function manuals - configured OPC UA Servers. Afterwards, we validate the results.
CRIS-Team Scopus Importer:2024-12-16
Keywords: charging station; cybersecurity; Machine-To-Machine; OPC Unified Architecture; penetration testing